Pengaruh Gamifikasi Terhadap Loyalitas Pelanggan Jaringan Hotel Internasional di Surabaya - Rean Mitasari; Erris Kusumawidjaya (P4M STIE Putra Bangsa, 2020)
In this 4.0 technology era, all industry sectors are required to make use of the internet and the latest technology for running their business process. In the tourism industry, especially accommodation, a system named gamification becomes one of the trends applied in the form of mobile applications done by various international hotel chains. By inserting game features such as tier (level), point, and reward, customers are expected to be more loyal by using those features embedded in the application. Therefore, this paper aims to examine to what extent gamification is able to influence customer loyalty of the international hotel chains in Surabaya. The data was collected by distributing an online questionnaire to the customers registered as loyalty program members of an international hotel chain in Surabaya. The study reveals that customer loyalty of the international hotel chain in Surabaya strongly influenced by the benefits obtained from the loyalty program provided in the form of the mobile applications.